A Note to Non-Traditional Systems of Public Transport - Anna Cerna; Jan Cerny (Communications - Scientific letters of the University of Zilina, 2006)
The paper deals with the following non-traditional (from the Czech point of view) solutions of public transport: • free competition of several providers, • use of heterogeneous rolling stock, • Dial-a-Ride systems and • integration with other systems.